If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(-4 + r) = -21 (-4 * 3 + r * 3) = -21 (-12 + 3r) = -21 Solving -12 + 3r = -21 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 3r = -21 + 12 Combine like terms: -12 + 12 = 0 0 + 3r = -21 + 12 3r = -21 + 12 Combine like terms: -21 + 12 = -9 3r = -9 Divide each side by '3'. r = -3 Simplifying r = -3
| 7x+17=80 | | an=17+(n-1)-3 | | 4(x)-17=31 | | 1/8=1/1/8 | | 1/3×5/8 | | 3(2+m)=12 | | F(x)=-5+1 | | 1/8=11/8/n | | 6h-4=2 | | 2z+23=27 | | 11-10x-7-4x=6 | | 4+2.2h= | | 70-21x=7x | | x+25=-23 | | 8+4e=28 | | q^3-q^2-30q=0 | | 2.5h-16=4h | | -4.2=-0.84(c+4) | | y=36x^2-48x-48 | | 2(x-3)+4=20 | | 61/4=3/5 | | 2.5h-16=4n | | 0=(-2/3)-3 | | 1.9z+19=-19 | | f(x)=36x^2-48x-48 | | -2/5v=-14 | | 5y=2y+78 | | x^4+x^3+7x^2+9x-18=0 | | 2(x-15)x/2 | | 3x^2+22x-10=0 | | -0.65(n+8)=3.9 | | 6d^6=90 |